Bexarotene Modulates Retinoid-X-Receptor Expression and Is Protective Against Neurotoxic Endoplasmic Reticulum Stress Response and Apoptotic Pathway Activation - Dheer, Yogita; Chitranshi, Nitin; Gupta, Veer; Abbasi, Mojdeh; Mirzaei, Mehdi; You, Yuyi; Chung, Roger; Graham, Stuart L.; Gupta, Vivek (Molecular neurobiology, 2018)
Retinoid X-receptors (RXRs) are members of the ligand-dependent transcription factor family of nuclear receptors that have gained recent research focus as potential targets for neurodegenerative disorders. Bexarotene is an RXR pharmacological agonist that is shown to be neuroprotective through its effects in promoting amyloid beta (Aβ) uptake by the glial cells in the brain. This study aimed to evaluate the dose-dependent effects of bexarotene on RXR expression in SH-SY5Y neuroblastoma cells and validate the drug effects in the brain in vivo. The protein expression studies were carried out using a combination of various drug treatment paradigms followed by expression analysis using Western blotting and immunofluorescence. Our study demonstrated that bexarotene promoted the expression of RXR α, β and γ isoforms at optimal concentrations in the cells and in the mice brain. Interestingly, a decreased RXR expression was identified in Alzheimer’s disease mouse model and in the cells that were treated with Aβ. Bexarotene treatment not only rescued the RXR expression loss caused by Aβ treatment ( p < 0.05) but also protected the cells against Aβ-induced ER stress ( p < 0.05) and pro-apoptotic BAD protein activation ( p < 0.05). In contrast, higher concentrations of bexarotene upregulated the ER stress proteins and led to BAD activation. Our study revealed that these downstream neurotoxic effects of high drug concentrations could be prevented by pharmacological targeting of the TrkB receptor. The ER stress and BAD activation induced by high concentrations of bexarotene were rescued by the TrkB agonist, 7,8 dihydroxyflavone ( p < 0.05) while TrkB inhibitor CTX-B treatment further exacerbated these effects. Together, these findings suggest a cross-talk of TrkB signalling with downstream effects of bexarotene toxicity and indicate that therapeutic targeting of RXRs could prevent the Aβ-induced molecular neurotoxic effects.